Determinants of Catch Sales in Ghanaian Artisanal Fisheries - Quagrainie, Kwamena K.; Chu, Jingjie (MDPI, 2019)
The study examined the determinants of catch sales of artisanal fishers through wealthy middle women in fishing communities of Ghana, often known as fish mothers or “fish mongers”. The effects of selected variables were examined with a double hurdle model. Self-financing was found to negatively affect the fishers’ sale of fish catch through fish mothers. The fishers were 19% less likely to sell to fish mothers if they self-finance, and that self-financing will result in a 10% downward unconditional change on the percentage of fish sold to the fish mothers. Factors that positively influenced the sale of fish catch through the fish mothers were price, percentage of high value fishes, size of boat, fishing experience, and number of fishing trips conducted in a year. The estimated average partial effects of boat size had the strongest effect with about 146% and 91% change, respectively on conditional and unconditional effect on the percentage of catch sales sold through the fish mothers. Overall, the study shows that long-term consistent economic and investment considerations such as investing in larger boats are important drivers for fishers’ choice of selling catches through fish mothers. The main implication of the results is that fishers need some economic leverage such as access to formal capital and financial resources to incentivize them to exercise control over their marketing activities so that they can receive a higher profit from their fishing operations. This is important for the sustainability of coastal fisheries communities and the sector as a whole. Artisanal fishers need resources such as low interest loans and market information systems that will enable them to negotiate prices for their fish catch with fish mothers.